Pengaruh Kompetensi Kerja Terhadap Kinerja Karyawan PT. Bank Sumut Syariah KCP Binjai - Afiyata, Yuri; Alam, Anjur Perkasa (Universitas Muhammadiyah Sumatera Utara, 2023)
This research was conducted to determine how much influence the independent variable, namely Work Competence (X) has on the dependent variable, namely Employee Performance (Y). The data used in this study are primary and secondary data. Primary data includes the distribution of questionnaires and secondary data includes books, journals, theses, and others. The analytical tool used in this study is SPSS 22.0 which includes normality test, linearity test, multicollinearity test, heteroscedasticity test, autocorrelation test, coefficient of determination (R), and t test. The results of the study indicate that work competence has a positive and significant effect on employee performance. This is evidenced by the results of statistical tests obtained a significance value of 0.013 and tcount of 2.653 (positive). Based on the provisions, if the significance value is 0.05 (0.013 0.05) and tcount ttable (2.653 1.697), then there is a significant contribution of Work Competence to Employee Performance. The positive and significant influence shows that this Work Competence variable has an influence on employee performance, so that employee performance will increase if work competence can be maintained properly.